Comparative immunogenicity of fowl cholera vaccine in Jinding ducks (Bangladesh Veterinarian, 2014)
This study compared the immunogenicity of alum-precipitated formalin-killed fowl cholera vaccines (BAU-FCV and LRI-FCV) in Jinding ducks. The ducks were divided into three groups (A = 14, B = 14, C = 12). Group A was inoculated with BAU- FCV 0.5 mL and group B with LRI- FCV 1.0 mL intramuscularly (im) at the age of six weeks and group C served as unvaccinated control. Booster vaccination was administered similarly at 11 weeks of age in groups A and B. Challenge infection was given to all birds two weeks after booster vaccination. Passive Haemagglutination Assay (PHA) antibody titres in group A were 59.4 ± 4.6 21 days after primary vaccination, 137.1 ± 21.8 15 days after booster vaccination, 100.6 ± 12.9 21 days after booster vaccination, and 256.0 ± 48.4 15 days after challenge. In group B, titres were 50.3 ± 6.5, 118.9 ± 9.1, 91.4 ± 12.9, 237.7 ± 51.7, respectively, whereas titres in group C remained at ?4.0 ± 0.0. The antibody titres were insignificant when compared between pre-vaccination and 21 days after primary vaccination in both vaccinated groups (A and B). PHA antibody titres of groups A were significantly (P < 0.0001) increased at 15 days after booster and in case of group B the antibody titres were insignificant. At 15 days after challenge the antibody titres were highly significant in both groups (A and B). There was no significant difference between the two vaccinated groups. Following challenge infection with virulent Pasteurella multocida 88.9% of birds vaccinated with BAU-FCV, and 77.8% of birds vaccinated with LRI-FCV survived, while all unvaccinated birds died. Both vaccines were safe and effective. DOI: http://dx.doi.org/10.3329/bvet.v30i2.18253 Bangl. vet. 2013. Vol. 30, No. 2, 41-45